Jewish theology for a postmodern age - Feldmann Kaye, Miriam (Littman library of Jewish civilization (Series), 2019)
Through a critical study of the writings of Rav Shagar and Tamar Ross, Miriam Feldmann Kaye asks how Jewish theology can survive the tide of postmodernism and its refutation of a single, objective, and ultimate truth, and suggests how aspects of postmodernism might be conceived of as a potential resource for rejuvenating religion.